Epulis fibrosa identified in a 6-year-old Japanese girl. Issue 1 (April 2016) - Hamada, Masakazu; Takasu, Ayako; Nomura, Ryota; Okawa, Rena; Nakano, Kazuhiko; Yura, Yoshiaki
Abstract: Epulis is a relatively common benign polypoid lesion that generally appears in the gingiva of individuals aged between 20 and 50 years. A 6-year-old Japanese girl came to our hospital for consultation regarding swelling of the marginal gingiva in the region between the maxillary left deciduous lateral incisor and canine. An intraoral examination revealed that the surface of the swollen mass was nonulcerated and smooth, and its color was similar to that of the surrounding gingival tissue. X-ray findings showed no calcified body or tooth germ malposition. The lesion was removed surgically under local anesthesia and histopathological findings showed it to be composed of fibrous connective tissue and blood vessels with minimal inflammatory cells, and covered by stratified squamous epithelium cells under the mucosa, which led to a diagnosis of epulis fibrosa. Patient prognosis has been good to date with no symptoms indicating recurrence.